Beware the evil eye: the evil eye in the Bible and the ancient world / Volume 3. The Bible and related sources - Elliott, John Hall (Cascade Books, 2016)
"This multi-volume study concentrates on the Evil Eye phenomenon in the ancient world, with new and extensive attention to mention of it in the Bible and the biblical communities of Israel and early Christianity. It is an up-to-date, comprehensive account of the extant ancient texts, amulets, and the modern research on this perennial topic. It is the first book-length study of all the biblical and related texts mentioning the Evil Eye.The study consists of four volumes, with material on the Evil Eye treated in roughly historical sequence from ancient Mesopotamia to Late Roman antiquity. This is the context within which Evil Eye belief and practice mentioned in the Bible is best understood. Volume One opens with an introductory overview of references to, and research on, the Evil Eye from the ancient past to the modern present (Chapter One). Chapter Two of Volume One examines Evil Eye belief and practice in ancient Mesopotamia and Egypt. Volume Two is devoted to evidence on the subject from ancient Greece and Rome. Within the geographical and cultural matrix detailed in these first two voumes, the evidence of Evil Eye belief and practice in the Bible is then examined (Volume Three). A final volume considers post-biblical evidence of Evil Eye belief and practice in Rabbinic Israel (Chapter One) and early Christianity (Chapter Two) through Late Antiquity (c. 600 CE). Concluding reflections on the import and implications of our study (Chapter Three) close this final volume." --